Role of phenolic acids and enzymes of phenylpropanoid pathway in resistance of chayote fruit (Sechium edule) against infestation by melon fly, Bactrocera cucurbitae. (6th January 2015) - Shivashankar, S.; Sumathi, M.; Krishnakumar, N.K.; Rao, V.K.
Abstract Melon fly is a serious pest of cucurbits all over the world causing huge losses to yield. However, the only exception is the chayote fruit (Sechium edule) that shows resistance to melon fly infestation. Studies on culture of melon fly indicated the absence of plant traits resisting oviposition on chayote fruit. However, the melon fly was unable to complete its life cycle successfully on chayote showing that factors inhibiting larval development in melon fly could be attributed to biochemical constituents. Studies were, therefore, carried out to compare the biochemical responses of chayote, a melon fly resistant species and bitter gourd, a susceptible species to melon fly infestation with regard to the levels of phenolic acids and activities of the enzymes of phenylpropanoid pathway (PPP) leading to synthesis of lignin. The resistant chayote exhibited significantly higher accumulation of lignin associated with higher activities of phenylalanine ammonia‐lyase (PAL), tyrosine ammonia‐lyase (TAL), cinnamyl alcohol dehydrogenase (CAD) and peroxidase (POD). On the contrary, the susceptible bitter gourd recorded lower activities of PAL, CAD and POD and a decreasing trend of TAL during infestation associated with a lower lignin content. The monomer composition of lignin in the resistant chayote showed twofold higher level of guaiacyl (G) and syringyl (S) units compared to susceptible bitter gourd and the G/S ratio during infestation increased in chayote while decreasing in bitter gourd. The levels of PPP intermediates, p‐coumaric acid was higher in chayote while p‐hydroxy benzoic acid, a chemo‐attractant, was higher in bitter gourd. Incorporation of p‐coumaric acid in the larval diet strongly inhibited larval growth even as p‐hydroxy benzoic acid promoted growth confirming the direct role of p‐coumaric acid in conferring resistance to chayote. The level of salicylic acid, a signal molecule involved in induction of defence response, was higher in chayote compared to bitter gourd. Chayote also exhibited higher level of activity of POD in the phloem exudates compared to bitter gourd. The higher concentration of sugars in exudates of chayote might act like signalling molecules causing activation of plant genes, especially of the phenylpropanoid biosynthesis pathway and possibly produce an osmotic effect inducing resistance against the melon fly. Thus, the study revealed that the resistance in chayote to melon fly infestation is a complex, multi‐layered process in which the activities of PPP enzymes generating phenolic intermediates leading to lignin biosynthesis and the composition of exudates appear to play significant roles. Besides, the study also indicated that different forms of lignin might play a role in the resistance of chayote against melon fly infestation.